Effect of pack carburizing and viscosity of quenching media on AISI 1010 steel - Agris Setiawan; Anggar Dipogusti (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2022)
Pack carburizing is a method of surface hardening of steel which is carried out by diffusing carbon into the material where the carbon is initially solid. This study aims to determine the effect of pack carburizing treatment on the microstructure and hardness of AISI 1010 steel. The material was then cooled slowly in the oven to a temperatur of 150oC which was then followed by air cooling. Single Quenching is then carried out by reheating the carburizing material to a temperature of 870oC and then holding it at that temperature for 60 minutes. Quenching is done by cooling the material quickly using a cooling medium of varying viscosity. The results of the composition test showed an increase in carbon content to 4.1159%. The results of microstructure observations showed that a massive pearlite structure was formed to a depth of ± 0.794 mm on the surface of the carburizing specimen. The results of the hardness test using the Vickers method showed that the hardness value of the raw material increased after carburizing to 217.88±5.13 HV due to the formation of a pearlite structure. With this increase in hardness, the application of AISI 1010 Steel material becomes wider. Keywords: Carburizing, Quenching, Viscosity, Hardness, Microstructure